2005
DOI: 10.1016/j.jfineco.2004.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Dealer behavior and trading systems in foreign exchange markets

Abstract: We study dealer behavior in the foreign exchange spot market using a detailed data set on the complete transactions of four dealers. There is strong support for an information effect in incoming trades. Although there is evidence that the information effect increases with trade size in direct bilateral trades, the direction of a trade seems to be more important. The large share of electronically brokered trades is probably responsible for this finding. In direct trades it is the initiating dealer that determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(85 citation statements)
references
References 35 publications
6
77
2
Order By: Relevance
“…The correlation between the first latent common factors of BAS and S2XW is 0.749. That the first latent common factor of BAS obtains such high correlations with the first common factors of P I and S2XW , two measures of Kyle's lambda (Kyle, 1985), conforms to the findings of Bjønnes and Rime (2005) that the adverse selection component of bid-ask spreads can be in excess of 50% of the bid-ask spread for exchange rates. The first latent common factor of ρ (1) is not highly correlated with the other trading cost measures with correlation coefficients with the first latent common factors of P I, BAS, and S2XW being -0.398, -0.139, and -0.120, respectively.…”
Section: Commonality In Pricing Errors and Trading Costssupporting
confidence: 78%
See 1 more Smart Citation
“…The correlation between the first latent common factors of BAS and S2XW is 0.749. That the first latent common factor of BAS obtains such high correlations with the first common factors of P I and S2XW , two measures of Kyle's lambda (Kyle, 1985), conforms to the findings of Bjønnes and Rime (2005) that the adverse selection component of bid-ask spreads can be in excess of 50% of the bid-ask spread for exchange rates. The first latent common factor of ρ (1) is not highly correlated with the other trading cost measures with correlation coefficients with the first latent common factors of P I, BAS, and S2XW being -0.398, -0.139, and -0.120, respectively.…”
Section: Commonality In Pricing Errors and Trading Costssupporting
confidence: 78%
“…Lyons (1995) finds evidence that both inventory-control and adverse selection affect prices. Bjønnes and Rime (2005), however, do not find evidence supporting prices being used to manage inventory; they find that adverse selection costs make up a large portion of bid-ask spreads.…”
Section: Related Literaturementioning
confidence: 89%
“…Moreover, many other researches focused on traders' overconfidence and proved its influence in forex market (Barber and Odean, 2000;Glaser and Weber, 2007;Oberlechner and Osler, 2008). In the same context, some works proved the impact of loss aversion and herding behaviour (Kim et al, 2004;O'Connelle and Teo, 2009) and some others showed the effects of feedback trading on forex market which is also considered important in forex trading (Aguirre and Said, 1999;Bjnnes and Rime, 2005;Laopodis, 2005).…”
Section: Related Workmentioning
confidence: 99%
“…Second, we show (footnote continued) (2007) analyzes inventory management of limit order traders using Euronext data. See also, among others, Hansch, Naik, and Viswanathan (1998) for London Stock Exchange data; Lyons (1995) or Bjønnes and Rime (2005) for foreign exchange markets. For NYSE specialist data, see, for example, Madhavan and Smidt (1993), Madhavan and Sofianos (1998), Hendershott andSeasholes (2007), or Panayid es (2007).…”
Section: Introductionmentioning
confidence: 99%